Crystal structure, phase transition and properties of indium(iii) sulfide. Issue 44 (9th November 2020) - Wyżga, Paweł; Carrillo-Cabrera, Wilder; Akselrud, Lev; Veremchuk, Igor; Wagler, Jörg; Hennig, Christoph; Tsirlin, Alexander A.; Leithe-Jasper, Andreas; Kroke, Edwin; Gumeniuk, Roman
Abstract : This report presents studies of crystal structures of α- and β-In2 S3 as well as a mechanism of the 1st order α–β phase transition. The structural part is supported by an analysis of thermoelectric properties and by DFT calculations. Abstract : Poly- and single-crystalline samples of In0.67 □0.33 In2 S4 thiospinel were obtained by various powder metallurgical and chemical vapor transport methods, respectively. All synthesized samples contained β-In0.67 □0.33 In2 S4 modification only, independent of the synthesis procedure. High-resolution powder X-ray diffraction (PXRD) experiments at 80 K enabled the observation of split tetragonal reflections (completely overlapped at room temperature), which prove the correctness of the crystal structure model accepted for the β-polymorph. Combining single-crystal XRD, transmission electron microscopy and selected-area electron diffraction studies, the presence of three twin domains in the as-grown crystals was confirmed. A high temperature PXRD study revealed both abrupt (in full widths at half maxima of main reflections and in unit-cell volume) and gradual (in intensity of satellites and c / a ratio) changes in the vicinity of the α–β phase transition. These observations, together with a clear endothermic peak in the heat capacity, the magnitude of enthalpy/entropy change and the temperature dependence of electrical resistivity (associated with hysteresis), hinted towards the 1st order type of transition. Three scenarios, based on Rietveld refinement analysis, were considered for the description of the crystal structure evolution from β- to α-modification, including the (3+3)D-modulated cubic structure at 693 K as an intermediate state during the β–α transformation. The Seebeck coefficient, electrical resistivity and thermal conductivity were not only influenced by phase transition, but also by annealing conditions (S-poor or S-rich atmosphere). Density functional theory calculations predicted semiconducting behavior of In0.67 □0.33 In2 S4, as well as instability of the fictitious InIn2 S4 thiospinel.